PENERAPAN MODEL PROBLEM BASED INSTRUCTION UNTUK MENINGKATKAN HASIL BELAJAR IPA TEMA 6 KELAS V SD - Retno Meilasyari; Ashari; Rintis Rizkia Pangestika (LPPM Universitas Cipta Mandiri, 2024)
The data obtained are the results of educators' activities in each cycle, the results of students' activities in each cycle, and the results of students' learning. Data analysis by calculating the overall score obtained is divided by the maximum score multiplied by 100%. The results of research on the application of the Problem Based Instruction model are: 1) increasing the application of the Problem Based Instruction model can improve learning outcomes for Science Theme 6 concerning Heat and its Transfer. The increase in the application of the Problem Based Instruction model can be seen from the overall average for the first cycle for educators, namely 89.85% of very good criteria, while the second cycle for educators is 93.99% of very good criteria. The increase in the application of the Problem Based Instruction model can also be seen from the overall average of cycle I for students, namely 92.06%, very good criteria, while cycle II for students, namely 94.90%, very good criteria. 2) the increase in student learning outcomes can be seen in each cycle, as evidenced by the increase in the percentage of student learning completion in the first learning session in cycle I, namely 37.93%, the criteria are very poor and it increases in the second lesson, namely 41.38%, the criteria are less, at the second meeting of the first learning cycle I, it was 51.72%, the criteria were insufficient and it increased in the second learning, namely 58.62%, the criteria were sufficient. Meanwhile, at the first learning meeting in cycle II, it was 62.07%, sufficient criteria and increased in the second learning, namely 68.97%, good criteria, at the second meeting, the first learning in cycle II was 79.31%, good criteria and increased in the second learning, namely 86 .21% very good criteria.